Habilidades de leitura na proposta de interação face a face do exame Celpe-Bras - Laura Marcia Luiza Ferreira (2012)
This study analyzes the reading activities proposed in the question scripts which form the Oral Proficiency Interview part of Celpe-Bras examination (Proficiency in Portuguese as a Foreign Language), issued by the Brazilian Government. Based on the theoretical framework about reading in a foreign language and on the fact that the aim of the face to face interview is to assess the candidate's oral performance, we look into the reading skills that underlie the question scripts proposed by the technical committee of the exam. Our corpus is limited to the tests of the first semester of 2004, 2007 and 2010. Firstly, we describe the textual genre that makes up the reading materials used during the face to face oral interaction. These materials are identified and categorized according to Askehave and Swales's (2001) textual genre classification methodology. We investigate the reading activities of textual genre groups most frequently used along the three years of analysis. The checklist developed by Dias (2009) to verify reading activities is adapted to the context of this work in order to identify the major reading skills that could be targeted by the question scripts. These skills are discussed by genre and year of application in order to find out which reading abilities are underlined by the questions related to different textual genres, such as advertisement, newspaper and magazine articles and if the reading abilities changed from one year to another. It was also possible to contrast the results of this research with the information provided by the Applicant's Manual regarding the preparation for the exam as well as its characterization. It was verified that the majority of the reading material proposed during the Oral Proficiency Interview was collected from the Brazilian press. We found that 83.3% of the samples used were made of clipping reports. Regarding the reading skills, we conclude that the question scripts mainly encourage the use of prior knowledge of the candidates, present diversified comprehension activities and help the reader construct and reconstruct the meaning of the original texts. Although the aim of the face to face oral interaction is to certify the oral proficiency of candidates for the Celpe-Bras, the reading skills that is demanded in this stage of evaluation are essential for the candidate to express themselves orally and to be able prove their ability to interact in Portuguese. It was also verified, by analyzing the question scripts, that the reading activities involve discursive and textual aspects of the texts proposed for reading during the face to face oral interaction.